(untitled) (Research, Society and Development, 2020)
The aim of this paper is to characterize the dynamic of Research, Development and Innovation (RD&I) network formation, and to identify the main sources of frictions and transaction costs related to the processes of Public-Private Partnerships (PPP) articulation by Embrapa Informática Agropecuária. Data collection on Embrapa’s PPP processes was done through documentary research and on-site visits. Four steps were identified for the PPP to be formalized: (i) partnership articulation (project proposal and submission); (ii) implementation/celebration; (iii) management and monitoring; and (iv) accountability and results. In the first two steps, the transaction costs involved are ex ante. In the third and fourth steps, the transaction costs are ex post. In addition to describing costs and assessing them as high or low, the article presents recent improved initiatives to minimize them at macro, meso and micro institutional level.